(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The protection of substantial equality involves abandoning the revolutionary equality that materialized in the so-called equality of all before the law, in order to achieve the ideal of equality of all within the law and, consequently, the prohibition of discrimination (direct or indirect). Thus, the right to equality encompasses the following dimensions: (i) affirmative action; (ii) equal opportunity measures; (iii) balanced participation measures. In this context, the planning of public policies is an important cross-cutting instrument for effectively integrating a gender perspective into all the activities of public authorities. Instruments to promote equality include public subsidies, institutional advertising, equality certificates in business matters and the creation of Councils for Effective Equality between Men and Women. Measures can also be established in the exercise of police power, such as the loss or suspension of subsidies to companies that do not comply with the relevant equality legislation. Translated with DeepL.com (free version)